Government Policy on Teacher Evaluation in Greece - Chrysos, Michail D. (Education Policy Analysis Archives, 2000)
After nearly two decades of freedom from evaluation, teachers in Greece became the focus of a new evaluation system. In 1998, reformers sought to raise the level of student performance by the regulation of teacher performance through a top-down evaluation system administered by the Greek Ministry of Education and Religous Affairs. The probable effects of this evaluation system on teachers' professional roles and development are analyzed.